The Effectiveness of Using Microteaching Books Based on Case Method and Team Based Project on Basic Teaching and Communication Skills of Biology Education Students - Widya Arwita; Hasruddin Hasruddin; Widia Ningsih; Rizal Mukra; Sailana Mira Rangkuty (Postgraduate, University of Mataram, 2025)
This study aims to determine the effectiveness of using microteaching books based on case method and team based project on basic teaching and communication skills. The type of research is development to produce a product and test the effectiveness of that product. The population is all 5th semester students of the biology education study program, FMIPA Unimed who take the microteaching course, the test sample is 30 students. The research design uses the Plomp development model, namely Analysis, Development, and Evaluation. Data collection is carried out at the analysis stage, then the development stage includes the distribution of assessment sheets to experts and response sheets to lecturers and students in the microteaching course. Meanwhile, the evaluation stage is carried out using observation sheets to assess basic teaching skills and communication skills. The data were analyzed using descriptive statistics and then categorized following the guidelines for categorizing needs, assessments, responses and communication skills. The results obtained indicate that the microteaching book is declared valid, has a fairly good level of practicality, and is effective in improving basic teaching skills and communication skills